A novel approach with concomitant laparoscopic uterine artery ligation and D&C as initial treatment for complicated gestational trophoblast disease in cesarean scar and cervical ectopic pregnancies - Yu-Han Lin; Yu-Che Ou; Fu-Tsai Kung (Elsevier, 2021)
Objective: Gestational trophoblast disease (GTD) in low-lying implantation ectopic pregnancy (LLIEP) is extremely rare. Surgical removal of GTD lesions which is the initial treatment of choice carries a high risk of intraoperative massive bleeding. Adequate management is challenging and inconclusive. Case report: We present two unusual cases with a diagnosis of GTD in advanced LLIEP. The first case had choriocarcinoma in cesarean scar and the second case had mole pregnancy in cervix. Both cases were managed with laparoscopy uterine artery ligations followed by transvaginal intrauterine curettage and vacuum aspiration with a small amount of surgical blood loss and then resumed regular menstruation. To understand the different surgical approaches and their potential advantages in managing such rare diseases, relevant cases in the literature were reviewed. Conclusion: Much attention should be paid to avoid massive bleeding at initial surgical intervention in patients with GTD in advanced LLIEP. This novel approach with combination of laparoscopic uterine artery ligations and evacuating curettage in selected patients is highly recommended to minimize surgical blood loss. The obvious advantages include technical feasibility, less surgery-related bleeding and potential fertility preservation.